Central Effects of 3-Iodothyronamine Reveal a Novel Role for Mitochondrial Monoamine Oxidases - Laurino, Annunziatina; Landucci, Elisa; Raimondi, Laura (Frontiers in Endocrinology, 2018)
3-Iodothyronamine (T1AM) is the last iodinated thyronamine generated from thyroid hormone alternative metabolism found circulating in rodents and in humans. So far, the physiopathological meaning of T1AM tissue levels is unknown. Much is instead known on T1AM pharmacological effects in rodents. Such evidence indicates that T1AM acutely modifies, with high potency and effectiveness, rodents’ metabolism and behavior, often showing inverted U-shaped dose–response curves. Although several possible targets for T1AM were identified, the mechanism underlying T1AM behavioral effects remains still elusive. T1AM pharmacokinetic features clearly indicate the central nervous system is not a preferential site for T1AM distribution but it is a site where T1AM levels are critically regulated, as it occurs for neuromodulators or neurotransmitters. We here summarize and discuss evidence supporting the hypothesis that central effects of T1AM derive from activation of intracellular and possibly extracellular pathways. In this respect, consisting evidence indicates the intracellular pathway is mediated by the product of T1AM phase-I non-microsomal oxidation, the 3-iodothryoacetic acid, while other data indicate a role for the trace amine-associated receptor, isoform 1, as membrane target of T1AM (extracellular pathway). Overall, these evidence might sustain the non-linear dose–effect curves typically observed when increasing T1AM doses are administered and reveal an interesting and yet unexplored link between thyroid, monoamine oxidases activity and histamine.